Issues on Role of Gender, Age and Qualification of faculties on Job Performance - Sapkota, Shiba Prasad (Nepalese Journal of Management Research, 2023)
The purpose of this study is to examine the association of gender, age and qualification of faculties with their perceived organizational justice and job performance. For this study faculties of 7 QAA certified colleges were taken through judgmental sampling. Sample size was 396 faculties determined by using slovins formula. Descriptive and cross-sectional research design was used. This study found there is no association of gender, age and qualification of faculties with job performance in Nepalese QAA Colleges. The strongest implication of this study is that fairness is an important motivator of job performance at work place.